Results on some robust multi-cost variational models - Savin Treanţă; Muhammad Uzair Awan; Muhammad Zakria Javed; Bandar Bin-Mohsin (AIMS Mathematics)
In this study, a new family of robust multiobjective fractional variational control problems was introduced and investigated. To this end, a dual model was associated with the class of problems. Further, by considering variants of convexity for the involved functionals (determined by curvilinear integrals that did not depend on the path), we provided some characterization and equivalence results for the considered models. Moreover, an illustrative numerical example was formulated.